A comprehensive approach to transdermal drug delivery through the skin: Ibuprofen derivatives in semi-solid formulations - Karolina Bilska; Anna Nowak; Anna Story; Grzegorz Story; Wiktoria Duchnik; Łukasz Kucharski; Paula Elżbieta Ossowicz-Rupniewska (Polish Pharmaceutical Society, 2023)
Abstract. This article presents a comprehensive study on the formulation and evaluation of pharmaceutical emulsions for topical drug delivery. The research focused on emulsions containing ibuprofen and its derivatives (sodium and L-lysine propyl ester salts), investigating their solubility, consistency, stability, and skin permeation. The study offers valuable insights into the development of effective pharmaceutical products. Background. Transdermal and topical drug delivery is a promising approach for the treatment of various medical conditions. Pharmaceutical emulsions provide an ideal platform for delivering active substances through the skin. The selection of emulsion ingredients, consistency, and stability play a critical role in determining the suitability of these formulations. Aim of the study. The primary aim of this study was to formulate and evaluate pharmaceutical emulsions containing ibuprofen and other active substances. Key objectives included assessing solubility, consistency, stability, and skin permeation characteristics of the emulsions. The study aimed to provide insights into the development of effective topical drug delivery systems. Material and methods. Solubility tests were conducted to select suitable emulsion ingredients. Various emulsions were prepared with different water-to-oil phase ratios. Rheology modifiers were added to enhance consistency. Quality control assessments were performed, including uniformity, consistency, stability, density, viscosity, and particle size analysis. The release of active substances from the formulations and their penetration and accumulation in the skin were determined. Results. The results revealed variations in viscosity, consistency, and stability among different formulations. Emulsion-based preparations demonstrated the highest accumulation of active substances in the skin, with formulation F1 (5294.617 μg/g skin) exhibiting the most promising results. The highest release of ibuprofen was observed from the formulation based on Celugel with the addition of [LysOPr][IBU] (F6) - approximately 7750 μg IBU/cm2, and the highest penetration of the active substance was obtained for the emulsion with the addition of IBU∙Na (F2) - 3300 μg IBU/cm2 after 24 hours of testing. Conclusion. This comprehensive study on pharmaceutical emulsions for topical drug delivery provides critical insights into the formulation and evaluation of cosmetic and pharmaceutical products. The findings highlight the importance of ingredient selection, consistency, and stability in the development of effective emulsion-based formulations. Furthermore, the study suggests that emulsion-based preparations have potential for topical applications, especially for more hydrophilic active substances. Future research can build on these results to enhance drug delivery systems and improve patient outcomes.